2001
DOI: 10.1007/s00232-001-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Domains of Mouse Connexin26 and -30 Affect Diffusional and Electrical Properties of Gap Junction Channels

Abstract: To evaluate the influence of intracellular domains of connexin (Cx) on channel transfer properties, we analyzed mouse connexin (Cx) Cx26 and Cx30, which show the most similar amino acid sequence identities within the family of gap junction proteins. These connexin genes are tightly linked on mouse chromosome 14. Functional studies were performed on transfected HeLa cells stably expressing both mouse connexins. When we examined homotypic intercellular transfer of microinjected neurobiotin and Lucifer yellow, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 45 publications
6
67
0
Order By: Relevance
“…We observed extensive transfer of LY at P0 and P8. Based on heterologous expression data, this can be interpreted as passage through gap junction channels comprising Cx26-only connexons (Manthey et al, 2001;Marziano et al, 2003). We observed junctional puncta predominantly labeled for Cx26 at these ages.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We observed extensive transfer of LY at P0 and P8. Based on heterologous expression data, this can be interpreted as passage through gap junction channels comprising Cx26-only connexons (Manthey et al, 2001;Marziano et al, 2003). We observed junctional puncta predominantly labeled for Cx26 at these ages.…”
Section: Discussionmentioning
confidence: 70%
“…The molecular permeability of gap junctions consisting of Cx26 and Cx30 have been studied previously in vitro using dyes of different charge and molecular weight (MW), including Lucifer yellow (LY) (charge, -2; MW, 443 Da) and Neurobiotin (NBN) (charge, ϩ1; MW, 287 Da). In heterologous expression systems, gap junctions between cells expressing Cx26 alone are permeable to LY and NBN (Manthey et al, 2001;Marziano et al, 2003). Gap junctions between cells expressing Cx30 alone transfer NBN but are impermeable to LY.…”
Section: Introductionmentioning
confidence: 99%
“…Using a Kruskal-Wallis test followed by Dunn's multiple comparison test, only Cx32/Cx30 and Cx47/Cx43 channels have G j that is significantly greater (*p Ͻ 0.001) than those of the corresponding control pairs (32/CTR and 30/CTR or 43/CTR and 47/CTR). studies have shown that homotypic channels containing only Cx32 (Elfgang et al, 1995), Cx43 (Elfgang et al, 1995), or Cx47 (Teubner et al, 2001;Orthmann-Murphy et al, 2007) are permeable to LY (MW, 443; valence, Ϫ2), but homotypic Cx30 channels are either minimally permeable (Beltramello et al, 2003) or impermeable (Manthey et al, 2001). As shown in Figure 5, when 0.1% LY was injected into one cell, we detected LY in the neighboring cell for pairs containing Cx47/Cx43 (Fig.…”
Section: Cx32/cx30 and Cx47/cx43 Channels Have Different Functional Pmentioning
confidence: 67%
“…Immunolabelling suggests that the small gap junction plaques that are present on the membranes of Deiters' cells in the Cx30 null mice are composed of Cx26, and there was no evidence for its upregulation, nor for the upregulation of some other connexin, with loss of Cx30 . The permeability properties of gap junction channels that contain Cx30, either alone or in heteromeric configuration with Cx26, are different from those formed of Cx26 only (Manthey et al, 2001;Marziano et al, 2003;Yum et al, 2007); Cx30 appears to play a role in restricting the passage of large anionic species. Thus, in the normal functionally mature organ of Corti anionic signalling molecules, such as IP3, c-AMP and ATP, may be unable to pass easily between Deiters' cells or between Hensen's and Deiters' cells.…”
Section: Discussionmentioning
confidence: 96%
“…There are 21 connexin genes in the human genome and 20 in that of the mouse (Bedner et al, 2012). There is some understanding of the varying biophysical properties of channels of different connexin composition (Kanaporis et al, 2011;Manthey et al, 2001;Yum et al, 2007) but the functional significance of expression of a particular connexin in a tissue is less clear.…”
Section: Introductionmentioning
confidence: 99%